Intellectual property in the global marketplace (Wiley, 1999)
With contributions from prestigious lawyers, economists, accountants, and consultants from around the world, Intellectual Property in the International Marketplace presents a highly complex subject in a user-friendly, organized manner. The two-volumes serve as an intellectual property compendium to business professionals and their counsel, helping them explore and answer intellectual property questions in business transactions in global settings. Volume I covers the methods for dealing with intellectual property in every type of business transaction, while Volume II covers the underlying general principles of international intellectual property law.